THE ROLE OF CHARACTER EDUCATION IN ENHANCING STUDENTS' CIVIC ENGAGEMENT: A SYSTEMATIC LITERATURE REVIEW - Mariah SM Purba; Ulung Napitu; Corry Corry; Bongguk Haloho (Program Pascasarjana UIN Sumatera Utara, 2025)
This study investigates how character education contributes to enhancing students? civic engagement through a Systematic Literature Review (SLR). Using the PRISMA 2020 framework, this review systematically identified, screened, and evaluated journal articles from Scopus, Web of Science, and Google Scholar published between 2015 and 2025. A total of 100 eligible peer-reviewed articles were included and analyzed using bibliometric mapping (VOSviewer) and narrative thematic synthesis. The VOSviewer network visualization positioned ?character education? as the most central and dominant keyword, strongly connected to ?student,? ?school,? ?implementation,? and ?values education,? indicating that character education functions as a core axis in civic-related educational discourse. The thematic findings reveal five main pathways through which character education strengthens civic engagement: (1) internalization of values that transforms moral understanding into meaningful civic actions, (2) civic identity formation that reinforces students? sense of collective responsibility, (3) development of prosocial skills and social responsibility that broadens everyday civic participation, (4) supportive school climate and institutional culture that provides democratic spaces for student involvement, and (5) digital citizenship that guides ethical civic participation in online environments. Overall, the findings confirm that character education serves as a ?moral engine? that supports sustainable, reflective, and inclusive civic engagement beyond normative civic knowledge. Future research should focus on more standardized civic engagement measurement, explore mediating factors such as civic identity and school climate, and further examine character-based civic engagement within digitally mediated contexts.